Farmer Empowerment in The Application Intercropping Technology of Chili Pepper (Capsicum Annum L.) and Cauliflower (Brassica Oleracea) in Bangodua District, Indramayu Regency - Kamilia Nur Asyaro Aida; M Tassim Billah; Yul Harry Bahar (Journal of Social Science, 2020)
This study aims to describe the empowerment of farmers in intercropping technology implementation, analyze the empowerment of farmers in the application of intercropping technology, and develop counseling strategies to increase the empowerment of farmers in the application of intercropping technology. Data were analyzed descriptively quantitatively, using multiple linear regression and determining extension strategies to increase farmer empowerment using SWOT analysis. The results showed that most farmers were of productive age (15-64 years old) with the dominant level of education in the low category (elementary / junior high) have monthly income (<Rp 4,000,000) but have experience in farming with the experienced category (11- 16 years old). Factors that affect the empowerment of farmers in intercropping technology implementation are the level of education, farming experience, the intensity of empowerment, and information availability while the factors that have no effect such as age, income level, and social physical environment. The strategy used to improve empowerment uses SWOT analysis so that the strategies. The need to do is increase innovations adoption in terms of the benefits of intercropping technology that can stabilize the harvest price accumulation. Information literacy can utilize demographic bonuses in the form of many productive ages through online e-marketing. It aligns the development of information with the synergy of cooperation between competing factors related to maximizing the potential of farm products in the field.